Sustainability of Communication, Organizational Culture, Cooperation, Trust and Leadership Style for Lecturer Commitments in Higher Education - Abd. Syakur; Tri Achmad Budi Susilo; Wike Wike; Rulam Ahmadi (Budapest International Research and Critics University, 2020)
This reserach was focused and related to effect of sustainability communication, bureaucracy structure and public support which have significant effect toward policy implementation performance and to execute Three Dharma (education, research and comunity service) in higher education. Communication, resources, bureaucracy structure and public support has its influence against disposition. In bureaucracy structure, public support has significant effect toward its main resources which is lecturer or its teaching staff. This study aimed to analyze the effect of communication and organizational culture toward leadership style, cooperation and trust also organizational commitment of lecturer in higher education viewed from its harmonization in executing three laws. Structural equation modeling (SEM) was used to analyze causality relation between variables. This study used survey method. Population in this study was lecturers in higher education. The total sample was determined 100 respondents from elevens Institution in higher education. Result of this study showed direct and positive significant effect of communication and organizational culture toward leadership style and cooperation also trust and organizational commitment of lecturers in higher education. There was no direct and positive significant effect of communication toward organizational culture. There was direct and positive significant effect toward cooperation and organizational commitment of lecturers to Institutions in higher education. There was direct and positive significant effect of work trust toward organizational commitment.